CONNECTIVITY OF MULTIVALUED REFLECTION GRAPHS IN COMPLEX DOMAINS - Amirova, Dilnoza; Aliqulov , Eshpulat (Educational Research in Universal Sciences, 2023)
In this article, a multi-valued reflection is created using derivative numbers in complex spaces. The dependency conditions of the reflection graph created using this collection are analyzed.